Emerging Roles of Cellular Metabolism in Regulating Dendritic Cell Subsets and Function - Du, Xingrong; Chapman, Nicole M.; Chi, Hongbo (Frontiers in Cell and Developmental Biology, 2018)
Dendritic cells (DCs) function as the bridge between innate and adaptive immunity and potently prime T cell activation. Recent studies have identified critical roles of metabolic pathways in orchestrating DC function. Understanding the metabolic basis of DC functional specification and regulation has the great potential to facilitate DC-based immunotherapy. In this review, we discuss the recent progress regarding the cellular metabolism in programming the function of different DC subsets in mice.